P39 The salford lung study in asthma: relationship between asthma control test (ACT) control status and future asthma exacerbations. (December 2018) - Woodcock, A; Jones, R; Jacques, L; Svedsater, H; Lay-Flurrie, J; Nelsen, L
Abstract : Introduction and objectives: The Salford Lung Study in asthma, an open-label, randomised controlled trial, evaluated the effectiveness of initiating once-daily inhaled fluticasone furoate/vilanterol (FF/VI) versus continuing usual care (UC) in a large, real-world population of patients with asthma in UK primary care. At Week 24, the odds of patients being ACT responders (total score ≥20 and/or improvement from baseline ≥3; primary endpoint) were significantly higher for FF/VI versus UC (odds ratio 2.00, 95% confidence interval: 1.70–2.34, p<0.0001). 1 In a pre-specified exploratory secondary analysis, we evaluated the impact of control status on future exacerbation risk. Methods: Patients aged ≥18 years with symptomatic asthma on an inhaled corticosteroid (ICS) ±long acting beta2 -agonist (LABA) were enrolled. The ACT questionnaire was completed at baseline and at Weeks 12, 24, 40, and 52. Exacerbations were recorded throughout the 52 week study period and annualised rates for each 12 week period following ACT completion were calculated by control status (not by randomised treatment group). Results: We included 4233 patients: mean age 50 years, mean baseline ACT score 16, mean severe exacerbation rate in previous year 0.6 (standard deviation [SD] 1.12). Annualised severe exacerbation rates between each ACT measurement were lowest in patients with well-controlled asthma and highest in patients with uncontrolled asthma (table 1). Conclusions: Asthma control status appears to be associated with future exacerbation risk. Funding: GSK (HZA115150/NCT01706198 ). Please refer to page A266 for declarations of interest related to this abstract. Reference: Woodcock A, et al. Lancet2017;390:2247–55.